Comparison of antioxidant properties of tamarillo (Cyphomandra betacea), cherry tomato (Solanumly copersicum var. cerasiform) and tomato (Lyopersicon esulentum) - Abdul Kadir, Noor Atiqah Aizan; Abdul Mutalib, Maisarah; Rahmat, Asmah (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2014)
The emerging studies suggest antioxidant may represent an important role in defence against certain diseases outlined the necessity of determining their contents in tamarillo (Cyphomandra betacea), cherry tomato (Solanum lycopersicum var. cerasiforme), and tomato (Lycopersicon esculentum). This study aims to determine the antioxidant capacity, total phenolic content and total flavonoid content in tamarillo, yellow cherry tomato, red cherry tomato, and tomato in 70% ethanol and water extracts. The ethanol extract showed the highest scavenging activity, ferric reducing activity, phenolic and flavonoid contents, whereas, the water extract showed higher value for antioxidant activity in ß-Carotene bleaching assay. Tamarillo showed the highest antioxidant activity (22.92 ± 3.60%, 28.89 ± 3.85%), scavenging activity (44.25 ± 0.82 μg/ml, 47.38 ± 1.11 μg/ml), ferric reducing activity (12.17 ± 0.53 μM Fe (II)/g, 3.72 ± 0.20 μM Fe (II)/g), phenolic content (7.63 ± 0.37 mg GAE/g edible portion, 1.83 ± 0.50 mg GAE/g edible portion) and flavonoid content (6.44 ± 0.16 mg CE/g edible portion, 2.22 ± 0.31 mg CE/g edible portion) in ethanol and water extracts respectively. For ethanol extracts a positive correlations existed (0.66 ≤ r ≥ 0.97) between ferric reducing activity, antioxidant activity, phenolic content and flavonoid content. While, in water extract correlation test revealed a positive correlations between antioxidant activity, ferric reducing activity and phenolic content (0.645 ≤ r ≥ 0.706) and between antioxidant activity and flavonoid content (r = 0.820). In conclusion, tamarillo exhibits the highest antioxidant capacity, phenolic content and also flavonoid content.